2009
DOI: 10.1007/s10534-009-9232-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cadmium on aquatic bird Cairina moschata

Abstract: The impact on palmiped Cairina moschata of two levels of dietary cadmium (Cd) contamination (C1: 1 mg kg(-1) and C10: 10 mg kg(-1)) was investigated on liver gene expression by real-time PCR. Genes involved in mitochondrial metabolism, in antioxidant defences, detoxification and in DNA damage repair were studied. Metallothionein (MT) protein levels and Cd bioaccumulation were also investigated in liver, kidneys and muscle. Male ducks were subjected to three periods of exposure: 10, 20 and 40 days. Cd was mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
2
10
1
Order By: Relevance
“…Although the current results were below concentrations observed in previous studies where adult Barau's Petrel from the Reunion island were reported to have accumulated 66.8 ± 31.8 lg g -1 (Kojadinovic et al 2007), low environmental levels such as 4.7 ± 0.7 lg g -1 in the liver of birds experimentally contaminated could trigger the appearance of sub-lethal effects (Lucia et al 2009). Lucia et al (2009) observed the appearance of oxidative stress and up-regulation of genes involved in mitochondrial metabolism.…”
Section: Trace Element Distribution and Toxicity Significancecontrasting
confidence: 91%
See 2 more Smart Citations
“…Although the current results were below concentrations observed in previous studies where adult Barau's Petrel from the Reunion island were reported to have accumulated 66.8 ± 31.8 lg g -1 (Kojadinovic et al 2007), low environmental levels such as 4.7 ± 0.7 lg g -1 in the liver of birds experimentally contaminated could trigger the appearance of sub-lethal effects (Lucia et al 2009). Lucia et al (2009) observed the appearance of oxidative stress and up-regulation of genes involved in mitochondrial metabolism.…”
Section: Trace Element Distribution and Toxicity Significancecontrasting
confidence: 91%
“…Lucia et al (2009) observed the appearance of oxidative stress and up-regulation of genes involved in mitochondrial metabolism. Cd is indeed able to inhibit the electron transfer chain and induce the production of reactive oxygen species (Wang et al 2004;Bertin and Averbeck 2006).…”
Section: Trace Element Distribution and Toxicity Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Cd toxicity might be more common among natural populations of vertebrates than has been appreciated to date. The ingestion of even trace quantities of Cd can influence not only the physiology and health of individual organisms, but also the demographics and the distribution of species (Larison et al 2000;Lucia et al 2009). Accompanying population declines, there have been two shifts in lesser scaup (Aythya affinis) demographics: a decrease in the proportion of young birds and an increase in the male-to-female ratio (Pollock and Machin 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide presence, even at limited concentrations, could lower such threshold temperature, considering the complex physiologic equilibrium that herbicides could disrupt; such temperature sensibility leads to an enhanced impact of herbicides in warm conditions [105]. Metal accumulation is enhanced by temperature increases [106].…”
Section: In Situ: Chemical Cocktail Interaction With Metals and Tempmentioning
confidence: 99%